b+36=7b

Simple and best practice solution for b+36=7b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b+36=7b equation:



b+36=7b
We move all terms to the left:
b+36-(7b)=0
We add all the numbers together, and all the variables
-6b+36=0
We move all terms containing b to the left, all other terms to the right
-6b=-36
b=-36/-6
b=+6

See similar equations:

| 2(x-4)5=-x+4 | | n9=6 | | f+9=35 | | 4x-3-14=-1 | | c+5=63 | | 3(x+4)+4x=-37 | | f6=6 | | x+36=38 | | 6x+2x+30=110 | | d−21=69 | | -34=-2y+4(y-5) | | –19f=11−18f | | b/23-5=13 | | j+14=32 | | c+42=50 | | 4q^2=64 | | 6+17b=14+16b | | 3z-32=z | | 18=10-2w | | 5.12p+7.1=-2.2 | | c+64=225 | | 4q^2-64=0 | | 7h=–19+6h | | 3u-39=u+1 | | 11w=-16=7w | | 3x-14x=-55 | | 8x=20=2x+34 | | 3x+12=2x-18 | | 1.2l+7=13.24 | | 11t-28=7t | | 34=5(x+9) | | –16g+–2g+5=–13 |

Equations solver categories